Safety and Effectiveness of Additional Apical Preparation using a Rotary Heat-treated Nickel-Titanium file with Larger Diameter and Minimum Taper in Retreatment of Curved Root Canals - Pinto, Jader Camilo [UNESP]; Torres, Fernanda Ferrari Esteves [UNESP]; Santos-Junior, Airton Oliveira [UNESP]; Duarte, Marco Antonio Hungaro; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Thieme, 2021)
Objective The aim of this study was to investigate the effect of additional apical preparation using the ProDesign Logic (PDL) 50/.01 rotary heat-treated nickel-titanium (NiTi) file with a larger diameter and minimal taper for retreatment of curved root canals. Materials and Methods Mesial curved root canals of 12 mandibular molars were prepared using PDL 25/.06 and filled using the continuous wave of condensation technique and AH Plus sealer. After retreatment using ProDesign S (PDS) 25/.08, PDL 25/.06 and PDL 35/05, a complementary procedure was performed with PDL 50/.01. Microcomputed tomography (micro-CT) scanning was performed before and after retreatment procedures. The cyclic fatigue resistance of unused PDS 25/.08, PDL 25/.06, PDL 35/.05 and PDL 50/.01 instruments (n = 12) was evaluated in a stainless-steel device. Statistical Analysis Data on the volumes of the root canals and the remaining filling materials were submitted to the paired t-test. Cyclic fatigue resistance data was submitted to one-way ANOVA and Tukey's tests (α = 0.05). Results Use of PDL 50/.01 decreased the remaining filling materials in the apical third (p < 0.05). The root canal volume was similar in the cervical and middle thirds before and after preparation using PDL 50/.01 (p > 0.05). PDL 50/.01 presented the highest cyclic fatigue resistance (p < 0.05). Conclusions Use of the PDL 50/.01 instrument as an additional apical preparation for retreatment of curved root canals improved filling material removal in the apical third, while maintaining the dentin in the cervical and middle thirds. In addition, PDL 50/.01 presented high-flexural resistance.
Keywords: Dental pulp cavity; retreatment; root canal preparation; X-ray microtomography